Peran Rahmah El-Yunusiyah dalam Pendidikan Islam Modern di Indonesia (1923-1969) - ’Aeni, Irma Nur; Fajriudin, Fajriudin; Marlina, Dina (Historia Madania: Jurnal Ilmu Sejarah, 2022)
Â The role of women is one of the most important in building a country, this shows the importance of the role of women in the nation and state. The purpose of this study was to determine the role of Muslim women in the development of education in the colonial era so as to create history in the struggle of women in Indonesia. The method used in this study uses historical research methods, including Heuristics, Verification (criticism), Interpretation and Historiography. During the colonial period, Indonesia was not only colonized physically, but also mentally. There are many ways to achieve independence, one of them is through education. Indonesia has female education fighters who are rarely known by the general public, namely Rahmah El-Yunusiyah. The result of her struggle in the field of education, Rahmah El-Yunusiyah succeeded in realizing the Diniyah Puteri School, which still exists today. The results of the research obtained by the author indicate that the backwardness of women, and the opposition to the existing education system at that time was very unlikely, this made Rahmah have the initiative to release her people from backwardness, one of the ways Rahmah achieved through education.